Quarantine Controversy: Kaci Hickox v. Governor Chris Christie - Gatter, Robert (The Hastings Center report, 2016)
Nurse Kaci Hickox is among the “Ebola Fighters” honored by Time magazine as its 2014 Person of the Year, having treated Ebola patients in Sierra Leone while volunteering with Médecins Sans Frontieres. When she returned to the United States in October 2014, she was quarantined in New Jersey for three days before returning home to Maine under the terms of a negotiated release. A year later, in October 2015, Hickox filed suit in federal court against Governor Chris Christie and New Jersey health officials, claiming that the quarantine violated her civil rights. Her complaint asserts that New Jersey officials lacked the authority to quarantine her because she did not pose a significant risk of transmission. The lawsuit raises important questions about disease-transmission risk, the inability of science to rule out certain theoretical risks, and the state's power to quarantine. It also demonstrates that population health depends on respecting individual liberty and using the best available epidemiological data to set public health policy.